Ankle Dorsiflexion in Childhood Cancer Patients: A Review of the Literature. Issue 6 (November 2015) - Beulertz, Julia; Wurz, Amanda; Culos-Reed, Nicole; Chamorro Viña, Carolina; Bloch, Wilhelm; Baumann, Freerk T.
Abstract : Background: Improved treatment protocols necessary for survival in pediatric oncology are associated with the development of serious late effects. Of particular importance, especially with regard to physical activity, may be ankle dorsiflexion (DF). Objective: This review summarizes the results of observational and exercise intervention studies exploring ankle DF-range of motion (DF-ROM) and/or ankle DF strength in pediatric oncology. Methods: PUBMED, Medline, Cochrane library, and SportDiscus were searched by 2 researchers using predefined search terms. The reference lists of included papers and Google scholar were then searched to that ensure all appropriate articles were included. Results: Twelve studies were identified and were observational (n = 8), providing information regarding the status of DF-ROM and/or DF strength, or intervention studies (n = 4) using exercise as a strategy to improve DF function. All observational studies reported some degree of impairment in ankle DF. Two intervention studies found a positive effect of exercise on ankle DF-ROM. Conclusion: The preliminary results suggest that pediatric cancer patients and survivors suffer from limitations in ankle DF with interventions varying in efficacy. Implication for Practice: It is hoped that this review will enhance the recognition of the limited ankle DF function in pediatric oncology and initiate further research programs focused on targeting and evaluating ankle DF.